THE USE OF WIRELESS SENSOR NETWORKS FOR MONITORING OF HUMAN-MADE OBJECTS - A. V. Sidorenko; K. S. Mulyarchik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The description of the characteristics of wireless sensor networks and the description of related research tasks have been given. The problem of ensuring of confidentiality of information transmitted over the wireless channel in sensor network has been addressed. The description of the monitoring system based on wireless sensor network has been provided, promising areas of application of such systems have been highlighted.